Using Modern Technology in Enhancing L2 (English) Reading Motivation among Undergraduate Students of Pakistan - Babar, Waqas Rafi; Maqsood, Muhammad Hasham; Khan, Tahir Jahan (Journal of Development and Social Sciences, 2025)
The study has been conducted to investigate the objectives of technology incorporation influences on students’ L2 (English) reading success, students’ motivation, and teachers’ skill. The study has tried to foster on students’ improvement in reading comprehension because empirical studies have simply addressed reading, L1 and L2 reading motivation. It has been observed that the score in reading comprehension has been declining among the students for numerous reasons such as avoiding and ignoring the incorporation of modern technology. Using the theory of a process model of L2 motivation, the researchers have designed three groups of the undergraduate students of BS English of NCBA&E Lahore. Three research questions were framed. Data have been collected from a sample of 85 students. The findings show that the incorporation of technology in the teaching methodology has improved, reading comprehension, motivation and teacher ability. Study has recommended the incorporation of technology with teaching and reading in English.